2016
DOI: 10.1161/atvbaha.116.307869
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Smooth Muscle STIM1 in Hypertension and Cardiovascular Dysfunction

Abstract: Objectives Chronic hypertension is the most critical risk factor for cardiovascular disease, heart failure, and stroke. Approach and Results Here we show that wild-type mice infused with Angiotensin II develop hypertension, cardiac hypertrophy, perivascular fibrosis and endothelial dysfunction with enhanced Stromal interaction molecule 1 (STIM1) expression in heart and vessels. All these pathologies were significantly blunted in mice lacking STIM1 specifically in smooth muscle (Stim1SMC−/−). Mechanistically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 56 publications
3
45
2
Order By: Relevance
“…STIM1 is an ER Ca 2ϩ sensor, which plays a critical role in the activation of Orai1 channels at the plasma membrane that mediate store-operated Ca 2ϩ entry. Smooth muscle-specific STIM1-deficient mice do not develop hypertension upon ANG II infusion; the vasculature of STIM1-deficient mice exhibits impaired ER stress responses and is protected from ANG II-induced endothelial dysfunction (464).…”
Section: Transient Receptor Potential Canonical Channels and Stromal mentioning
confidence: 97%
See 2 more Smart Citations
“…STIM1 is an ER Ca 2ϩ sensor, which plays a critical role in the activation of Orai1 channels at the plasma membrane that mediate store-operated Ca 2ϩ entry. Smooth muscle-specific STIM1-deficient mice do not develop hypertension upon ANG II infusion; the vasculature of STIM1-deficient mice exhibits impaired ER stress responses and is protected from ANG II-induced endothelial dysfunction (464).…”
Section: Transient Receptor Potential Canonical Channels and Stromal mentioning
confidence: 97%
“…Moreover, ER stress and UPR have been shown to play causative roles in various ANG II-induced pathologies, including brain (1216) and vascular (465,587) regulation of hypertension, endothelial dysfunction (465), cardiac hypertrophy and fibrosis (465), and vascular hypertrophy and fibrosis (465,989,1035). Specifically, CHOPϪ/Ϫ mice are protected from ANG IIinduced NADPH oxidase activation, hypertension, and cardiovascular pathology (464). ANG II-induced ER stress exists downstream of the ADAM17/EGFR transactivation cascade (1034,1035) and stromal interaction molecule 1 (STIM1) induction (464), and upstream of cardiac (465) and renal TGF-␤ induction (1118), vascular apoptotic pathway (989), and brain SFO NF-B activation (1218).…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
See 1 more Smart Citation
“…Since STIM1 is a key regulator of Ca 2+ homeostasis for supporting communications between the ER/SR and the plasma membrane, its upregulation could lead to direct or indirect ER/SR stress, as well as dictating the development of cardiovascular complications in hypertensive conditions. Wild-type mice infused with angiotensin II have been shown to develop hypertension, cardiac hypertrophy, perivascular fibrosis and endothelial dysfunction associated with enhanced STIM1 expression in heart and blood vessels, in study by Kassan et al (2016). The same authors reported that STIM1 up-regulation during angiotensin IIinduced hypertension was associated with enhanced ER/SR stress through TGF-β and NADPH oxidase-dependent pathways.…”
Section: Store-operated Ca 2+ Pathways -Stim1/orai 1 In Hypertension mentioning
confidence: 95%
“…Conversely, their dysregulation promotes several pathophysiologies, including atherosclerosis, arterial stenosis, thrombosis, and hypertension (Ruhle and Trebak, 2013;Tanwar et al, 2017). There is a strong correlation between hypertension and enhanced STIM and/or Orai protein expression (Kassan et al, 2016;Pulina et al, 2013;Spinelli and Trebak, 2016;Zhang and Trebak, 2011). It has been proposed that augmented Ca 2+ influx through SOCE pathways, STIM1/Orai 1, may contribute in potentiating vascular reactivity (Giachini et al, , 2012 and vascular tone and force generation (Goulopoulou and Webb, 2014;Kitazono et al, 2002;Tanwar et al, 2017) (Fig.…”
Section: Store-operated Ca 2+ Pathways -Stim1/orai 1 In Hypertension mentioning
confidence: 99%